Penggunaan Citra Satelit Aqua/Terra MODIS untuk Pemetaan Suhu Permukaan Tanah di Kabupaten Bandung Tahun 2018-2022 - Tidiesya, Tsabita; Khairunnisa, Nada; Jasmine, Kirana Aisha; Mataburu, Ilham Badaruddin; Hijrawadi, Sony Nugratama (Jurnal Pendidikan Geografi Undiksha, 2025)
Bandung Regency experiences significant dynamics of surface temperature change due to rapid development and land use change. This study aims to analyze the dynamics of Land Surface Temperature (LST) in Bandung Regency during the 2018-2022 period and identify the factors that influence it. The method used is the analysis of Modis Terra Land Surface Temperature and Emissivity 8-Day Global satellite image data using Google Earth Engine to produce average surface temperature distribution data presented in the form of graphs and temporal maps. The results showed surface temperature variations ranging from 18°C to 32°C, with distribution patterns influenced by topography and land cover. The mountain-dominated southern region has temperatures of 18-20°C, while the northern and northeastern regions reach 28-32°C. There is a seasonal pattern where the September-October period shows the highest temperatures, while June-July is relatively stable. Land conversion, which accounts for 34,327.48 hectares (49.25%) of total land change in the BMA, contributes significantly to surface temperature dynamics. It can be concluded that land cover change, infrastructure development activities, and topographic factors have a major influence on surface temperature variability in Bandung Regency, so that stricter spatial management and integrated afforestation programs are needed to mitigate the impact of increasing surface temperatures.